Proposal For an environmental risk management approach applied in Algerian ports: the case of Bethioua port (Algeria) - M SMAIAH; L BAHMED (International Journal of Environmental Engineering, 2016)
Background Noncompliance of operators with work procedures is a recurrent problem. This human behavior has been said to be situational and studied by many different approaches (ergonomic and others), which consider the noncompliance with work procedures to be obvious and seek to analyze its causes as well as consequences. Methods The object of the proposed method is to solve this problem by focusing on the performance of work procedures and ensuring improved performance on a continuous basis. Results This study has multiple results: (1) assessment of the work procedures' performance by a multicriteria approach; (2) the use of a continuous improvement approach as a framework for the sustainability of the assessment method of work procedures' performance; and (3) adaptation of the Stop-Card as a facilitator support for continuous improvement of work procedures. Conclusion The proposed method emphasizes to put in value the inputs of continuous improvement of the work procedures in relation with the conventional approaches which adopt the obvious evidence of the noncompliance to the working procedures and seek to analyze the cause–effect relationships related to this unacceptable phenomenon, especially in strategic industry.